LOS ACUERDOS INTERNACIONALES SOBRE INVERSIÓN, OTRO OBSTÁCULO PARA EL DESARROLLO DE AMÉRICA LATINA 1 - Zabalo, Patxi (2008)
The international agreements on investments, so much the bilateral as the insertions in tried economic integration, suppose the almost total opening to the foreign investment and its protection, once established in the country. For the differences prevents an exterritorial system of solution of differences in which the businesses can demand directly to the states. The multiplication of this type of demands in instances of international arbitration is flowing into in compensations multimillionaires and intolerable limitations of the national sovereignty to establish public politics. These agreements have proliferated in Latin America during the last two decades and the accumulated experience does not leave place to doubts on its gravity. Therefore it presses to apply the Calvo doctrine, in which the possible conflicts should be resolved in the local courts, remaining preserve the resource to the international arbitration. Thus, recovering their full jurisdictional sovereignty, the Latin-American states will be in better conditions to carry out political of development.